Education of Nurses in Rural Primary Health Cares to Improve Vital Care of Newborns: A Community-Based Research in Nigeria. - Clementina, Nkiru Eze; Christiana, Elusoji I.; Christiana, Nkiru Okafor; Augusta, Nkechi Emeh; Amuchechukwu, Veronica Nwafor; Ihuoma, Obi A.; Odinakachukwu, Onyeabor Juliana; Ohams, Ohanme Eugene (Kabale University, 2024)
This study was designed to ascertain the level of knowledge and the degree of practice of the components of Essential New-born care (ENC), and the effects of a training programme on the knowledge and practice of ENC among nurses in rural Primary Health Cares (PHCs) in South East Nigeria. This study was a one group pre-test and post-test intervention design. The components of ENC considered were: New-Born Initiation of Breastfeeding, Thermoregulation, New-Born Cord Care, Newborn Eye Care, Initiation of Breathing and Administration of Vitamin K. A Neonatal care Knowledge and Practice Assessment (NCKPA) Questionnaire tested for validity and reliability, with a Spearman’s correlation coefficient of 0.81, was used for data collection among the (96) available nurses (All female). There was significant improvement in the level of knowledge and extent of practice of the components of ENC following the training programme. Despite the improvement, there were gaps in knowledge and practice of the components of ENC amongst the nurses in rural PHCs and affected were the level of knowledge of Eye care 40(41.6%) - per-intervention, and least knowledge of cord care 70 (72.9%) and eye care 90(93.8%) - post-intervention. Increase in knowledge corresponded with increase in good practice of ENC. The concern with knowledge transfer and translation of knowledge into practice could be achieved by pre-service and in-service education, update courses and workshops, and this will empower the nurses, getting them familiar with current trends and practices for improved child survival rate.